Childhood asthma in South London: trends in prevalence and use of medical services 1991–2002. Issue 5 (31st January 2006) - Butland, B K; Strachan, D P; Crawley-Boevey, E E; Anderson, H R
Abstract : Background: Hospital admission rates for asthma in Britain rose during the 1980s and fell during the 1990s, but less is known about recent trends in the prevalence of asthma. Methods: In 1991 and 2002 the same questionnaire was distributed to parents of all school pupils in year 3 (aged 7–8 years) in the London borough of Croydon. Parents of currently wheezy children were then invited for home interview (100% targeted in 1991, 66% in 2002). Results: The prevalence of wheeze during the previous year increased from 12.9% in 1991 to 17.8% in 2002 (prevalence ratio 1.39 (95% CI 1.23 to 1.56)). Increases were observed in frequent (1.54 (95% CI 1.16 to 2.03)) and infrequent attacks, severe speech limiting episodes (2.25 (95% CI 1.34 to 3.77)), and night waking (1.36 (95% CI 1.07 to 1.72)), and in the reported use of steroids (19.9% v 64.1% of currently wheezy children). Nevertheless, the proportions reporting a visit to the GP at his/her surgery for wheeze in the previous year (prevalence ratio 1.15 (95% CI 0.91 to 1.45)) or an outpatient visit (0.98 (95% CI 0.49 to 1.94)) changed little and an increase in reported casualty attendance (1.66 (95% CI 0.89 to 3.07)) was non-significant. Conclusions: There is evidence of an increase in the prevalence of asthma among British primary school children between 1991 and 2002. The absence of a corresponding increase in health service utilisation data may reflect more widespread prophylactic treatment and/or changes in the use and provision of medical services.